A study of molybdena catalysts in ethanol oxidation. Part 2. Alumina‐supported and silica‐doped alumina‐supported MoO3. Issue 12 (1st September 2021) - Pampararo, Giovanni; Garbarino, Gabriella; Ardoino, Niccolò; Riani, Paola; Busca, Guido
Abstract: BACKGROUND: γ‐Al2 O3 and silica‐doped aluminas are largely used supports for industrial catalysts. The addition of silica to alumina modifies its acid–base properties, also affecting its dispersion ability of supported species. In this paper, investigations on the silica doping effect in alumina‐supported MoO3 catalysts, developed for the oxidative dehydrogenation process of ethanol to acetaldehyde, are reported. RESULTS: MoO3 (1÷12% wtMoO3 /wtsupport ) supported over pure γ‐Al2 O3, SiO2 (1 and 5 wt.%) doped γ‐Al2 O3 were prepared by incipient wetness impregnation. Catalysts were studied and extensively characterized structurally, morphologically, and chemically. All samples were tested in ethanol oxidative dehydrogenation in Temperature Programmed Surface Reaction conditions. Best performing catalysts were also tested in steady‐state and time‐on‐stream experiments. At 573 K, the best acetaldehyde yield (60% in steady state conditions) was found on 12 wt.% MoO3 over 1 wt.% SiO2 on alumina. The slight deactivation after 8 h on stream (10% activity loss) is attributed to a limited MoO3 loss by volatilization. CONCLUSION: The investigated catalysts are active and allow quite a high yield to acetaldehyde. The addition of silica to alumina increases both the conversion of ethanol and the selectivity to acetaldehyde, and reduces MoO3 volatilization, due to the higher activity of monomeric molybdates with respect to polymeric ones. The high acidity of the catalysts limits oxydehydrogenation yield, catalyzing competitive reaction to ethylene. © 2021 Society of Chemical Industry (SCI).